Enhanced Depth Imaging Optical Coherence Tomography: A New Way Measuring Choroidal Thickness in Pregnant Women - Jun Zhang; Huiyun Wang; Qiubo Yu; Qihu Tong; Qinkang Lu (Journal of Ophthalmology)
The body changes markedly during pregnancy; each system behaves differently from a nonpregnant state. As the eyes are the only windows to see directly what is going on in the internal environment, more and more researches have been done to explain the association between ocular changes and the physiological and pathological changes during pregnancy. The choroid is one of the critical parts of the eye, providing nutrition. And abnormal choroid may result in ocular dysfunction and visual problems. As the optical coherence tomography develops, a rapid, direct, noninvasive, and nontoxic way is available to obtain the choroid situation of pregnant women, which may explain the mechanism of pregnancy-related eye diseases. This review would summarize relevant original articles published from January 1, 2008 to December 1, 2016 to assess the changes of choroidal thickness (CT) with enhanced depth imaging optical coherence tomography (EDI-OCT) during pregnancy. And the relationship between choroidal thickness changes and pregnancy remains uncertain. To our knowledge, this is the first review of EDI-OCT in assessing the choroidal thickness of the pregnant women.